2011
DOI: 10.1111/j.1439-0272.2010.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine on spermatogenesis in adult albino rats

Abstract: This study aimed to assess the effects of nicotine on spermatogenesis in 140 mature male albino rats divided into group A (controls), group B (sham controls), group C (nicotine treated) and group D (nicotine withdrawal). Group C was subdivided into CI, CII, CIII according to the dose of injected nicotine (0.2, 0.4 and 0.6 mg nicotine per 100 g per day), where each subgroup was further subdivided according to the treatment duration into subgroups a, b and c that received nicotine for 2, 4 and 8 weeks. Group D r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
6
16
0
Order By: Relevance
“…It has been reported that NIC causes Leydig cells dysfunction and decreases the testosterone level . According to relevant studies, increase in the dose of NIC leads to the reduction in germ cell proliferation . Due to the importance of Leydig cells in the secretion of testosterone, which plays the key role in spermatogenesis, destruction of these cells can be a major cause of apoptosis and cell death elevation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that NIC causes Leydig cells dysfunction and decreases the testosterone level . According to relevant studies, increase in the dose of NIC leads to the reduction in germ cell proliferation . Due to the importance of Leydig cells in the secretion of testosterone, which plays the key role in spermatogenesis, destruction of these cells can be a major cause of apoptosis and cell death elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NIC causes disturbances in the functions of cells and induces oxidative stress and apoptosis through exerting effects on acetylcholine receptors. It has been shown that NIC causes damages to the reproductive system via increase in the levels of the ROS and MDA in reproductive tissues . Cotinine, a NIC metabolite, similar to NIC, enhances production of free radicals and ROS in testicular tissue and can lead to the lipid peroxidation generation ultimately inducing cellular damages …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic pyrethroid insecticides usage has increased lately due to the need to replace common organophosphate insecticides following use restrictions. A consequence of its increased availability, use and broad‐spectrum applicability, there is widespread exposure among the general population (Nesseim et al ., ; Li et al ., ). Diet and household dust are the primary sources of exposure to pyrethroids among nonoccupationally exposed individuals (Julien et al ., ).…”
Section: Introductionmentioning
confidence: 97%